2015
DOI: 10.1089/aid.2014.0168
|View full text |Cite
|
Sign up to set email alerts
|

Viral Genetic Diversity and Polymorphisms in a Cohort of HIV-1-Infected Patients Eligible for Initiation of Antiretroviral Therapy in Abuja, Nigeria

Abstract: Studying the genetic diversity and natural polymorphisms of HIV-1 would benefit our understanding of HIV drug resistance (HIVDR) development and predict treatment outcomes. In this study, we have characterized the HIV-1 genetic diversity and natural polymorphisms at the 5′ region of the pol gene encompassing the protease (PR) and reverse transcriptase (RT) from 271 plasma specimens collected in 2008 from HIV-1-infected patients who were eligible for initiating antiretroviral therapy in Abuja (Nigeria). The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
(61 reference statements)
2
11
1
Order By: Relevance
“…Hence, the larger size of our dataset, the relatively long time-window of sampling, and the use of state-of-the-art phylodynamic methods enabled us to perform the first in-depth nationwide HIV-1 phylodynamic study in Nigeria. In line with other previous studies from different geographic regions in Nigeria, we found that CRF02_AG, CRF43_02G and subtype G were the most prevalent strains (previous estimates ranging www.nature.com/scientificreports www.nature.com/scientificreports/ from 19-60% for CRF02_AG and 22-50% for subtype G [18][19][20][21][22][23][24][25]62 ). The prevalence of CRF43_02G has only been reported in one previous study from Abuja (estimated to 19%) 21 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, the larger size of our dataset, the relatively long time-window of sampling, and the use of state-of-the-art phylodynamic methods enabled us to perform the first in-depth nationwide HIV-1 phylodynamic study in Nigeria. In line with other previous studies from different geographic regions in Nigeria, we found that CRF02_AG, CRF43_02G and subtype G were the most prevalent strains (previous estimates ranging www.nature.com/scientificreports www.nature.com/scientificreports/ from 19-60% for CRF02_AG and 22-50% for subtype G [18][19][20][21][22][23][24][25]62 ). The prevalence of CRF43_02G has only been reported in one previous study from Abuja (estimated to 19%) 21 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have identified subtype G and the CRF02_AG as the most common HIV-1 variants in Nigeria [17][18][19][20] . In addition, the CRF43_02G was recently shown to be highly prevalent in the capital Abuja 21 . However, the estimates of each strain's contribution to the Nigerian HIV-1 epidemic have varied considerably, with frequency estimates ranging from 22-50% for subtype G, and 19-60% for the CRF02_AG [18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce cost, in-house and DBS- applicable assays were developed using degenerate amplification and sequencing primers (290,291). For instance, the in-house assay developed by the CDC has been used for population-based surveys using plasma specimens from Nigeria (292) and DBS specimens from Vietnam (290), Malawi (290), Nigeria (290), Kenya (142), and Uganda (293). The reagent cost of the assay is 20 to 25% lower than that of the commercial test kit method.…”
Section: Genotyping Methodologiesmentioning
confidence: 99%
“…Combinations of the SP, DT, and UG RDTs are used in Uganda, Malawi, Zambia, Nigeria, and other countries ( 4 , 24 , 25 ). Ideally, the suitability of HIV control strategies and algorithms for screening specific populations should be evaluated in the appropriate context of test availability, antigen/antibody targets of each test, local seroprevalence, genetic diversity, and risk of infection in the populations being examined as well as local operational factors and laboratory qualifications ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%